Surface coating for protecting concrete tower drum of wind power mixed tower

By using the surface coating made of powder component A and liquid component B, the problems of weak bonding, poor crack resistance and poor durability of the protective material of the wind power mixed tower concrete tower are solved, and the comprehensive improvement of high adhesion, crack resistance and durability are achieved, and the service life of the tower is extended.

CN119505624APending Publication Date: 2025-02-25HUNAN GUTEBANG CIVIL TECH DEV CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510079451.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing wind power mixed tower concrete tower protective materials have weak bonding, poor crack resistance and poor durability, making it difficult to effectively protect in harsh environments.

Method used

The surface coating consisting of powder A and liquid B is adopted. The powder A component includes ordinary silicate cement, double-fly powder, silica fume powder, etc., and the liquid B component includes epoxy modified acrylic emulsion and aqueous fluorocarbon emulsion, etc., and is uniformly prepared by mechanical stirring.

Benefits of technology

It has achieved the characteristics of high bonding performance, excellent crack resistance, good corrosion resistance, strong weather resistance and good durability of the surface coating, significantly improving the durability of the concrete tower of the wind power mixed tower and extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a surface coating for protecting a concrete tower drum of a wind power mixing tower, the surface coating comprises a powder component A and a liquid component B, and a finished product is obtained by mechanically stirring the powder component A and the liquid component B uniformly. The surface coating has the characteristics of good bonding performance, excellent crack resistance, good corrosion resistance, strong weather resistance and good durability, is suitable for surface protection of the concrete tower drum of the wind power mixed tower, improves the durability of the concrete tower drum of the wind power mixed tower, and prolongs the service life of the concrete tower drum of the wind power mixed tower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer-based functional composite materials, and in particular to a surface coating for protecting a concrete tower of a wind power hybrid tower. Background Art

[0002] As the world's demand for new energy continues to increase, wind power science and technology has been greatly developed, and wind turbine capacity has been continuously improved, which has put forward higher requirements on the quality of wind turbine towers. Wind power concrete towers have been vigorously developed due to their cost advantages and low maintenance costs. Due to the rich wind energy resources on the plateau and offshore, wind power towers are generally built in outdoor environments such as plateaus and offshore, which makes the wind power towers exposed to wind and rain erosion, high and low temperature cycles, strong ultraviolet radiation and acid, alkali and salt corrosion for a long time. This requires the wind power tower to have extremely high corrosion resistance, weather resistance and durability to ensure that it has a long service life. The strength of wind power concrete towers is generally above C70, with a dense structure and good corrosion resistance. However, the higher the concrete strength grade, the more likely it is to crack. Once fine cracks appear in the wind power concrete tower components, moisture and corrosive gases in the air will penetrate into the concrete along the cracks, slowly corrode the steel bars inside the concrete, and cause structural damage inside the concrete, greatly reducing the mechanical properties of the wind power concrete tower and reducing the durability of the wind power concrete tower. In addition to cracking, the concrete tower components of wind power towers also have surface defects such as pits, exposed steel bars, and peeling caused by other reasons. These defects are more likely to be magnified in long-term outdoor complex environments, which greatly affects the durability of wind power tower concrete towers. In order to improve the durability of wind power tower concrete towers and extend the service life of wind power tower concrete towers, it is necessary to use suitable protective materials to treat the surface of wind power tower concrete towers for corrosion protection. Commonly used protective materials include acrylic, polyurethane, epoxy, silane, etc. The wind power tower concrete tower has a high strength grade and a smooth concrete surface. Ordinary acrylic and polyurethane protective materials have weak adhesion and are prone to falling off. Epoxy and silane are prone to cracking in harsh environments, thereby affecting durability. How to prepare a wind power tower concrete tower protective surface coating material with good bonding performance, excellent crack resistance, good corrosion resistance, strong weather resistance, and good durability has become a technical problem that needs to be solved urgently. Summary of the invention

[0003] In view of the problems of weak adhesion, poor crack resistance and poor durability of existing wind turbine concrete tower protection materials, the purpose of the present invention is to provide a surface coating for protecting wind turbine concrete towers. The surface coating has the characteristics of good adhesion, excellent crack resistance, good corrosion resistance, strong weather resistance and good durability. It is suitable for the surface protection of wind turbine concrete towers, improves the durability of wind turbine concrete towers, and extends the service life of wind turbine concrete towers.

[0004] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: A surface coating for protecting a wind power concrete tower, comprising a powder component A and a liquid component B; The powder A component includes the following components in parts by weight: 30~60 parts of ordinary Portland cement; 30~55 portions of double fly powder; Silica fume powder 4-10 parts; Superplasticizer 0.5~1.5 parts; Anti-settling agent 0.1~0.3 parts; 0.3~1 part of nano cerium oxide; 3-6 parts of silicate; The liquid material B component includes the following components in parts by weight: Epoxy modified acrylic emulsion 30-55 parts; 20~35 parts of water-based fluorocarbon emulsion 20~40 parts of deionized water; 0.2~0.5 parts of fungicide; Defoaming agent 0.5~2 parts; The mass ratio of the powder component A to the liquid component B is 100:60-80.

[0005] Furthermore, the preparation steps of the epoxy-modified acrylic emulsion are as follows: S1, mixing an epoxy resin with an acid anhydride containing a double bond, and carrying out a condensation reaction under the action of a promoter and an inhibitor to obtain a double-bond modified epoxy resin; S2. Mix the double-bond modified epoxy resin with hydroxypropyl methacrylate, methacrylic acid, sodium allyl sulfonate and hydroxyalkyl methacrylate, and carry out free radical polymerization under the action of a chain transfer agent, an initiator and an inhibitor to obtain an epoxy-modified acrylic emulsion.

[0006] Furthermore, in step S1, the epoxy resin is bis((3,4-epoxycyclohexyl)methyl)adipate. The preferred epoxy resin of the present invention contains highly active and polar epoxy groups, which can react with the active groups on the concrete interface to form stable chemical bonds, thereby greatly improving the bonding performance with the concrete.

[0007] Furthermore, in step S1, the acid anhydride is itaconic anhydride. The acid anhydride of the present invention has unsaturated double bonds and can react with epoxy resin. By introducing active double bonds on epoxy resin, it can participate in free radical polymerization reaction and provide epoxy groups for polymer macromolecules to obtain high bonding performance.

[0008] Furthermore, in step S1, the mass ratio of the acid anhydride to the epoxy resin is 3-10:45-60.

[0009] Furthermore, in step S1, N,N-dipropyl-1-propylamine is used as a promoter, hydroquinone is used as an inhibitor, and the mass ratio of promoter, inhibitor and epoxy resin is 2-6: 0.03-0.05: 45-60. The present invention can shorten the condensation reaction time and reduce the reaction temperature through the catalytic effect of the promoter, and the introduction of the inhibitor can prevent the copolymerization of double bonds in the reaction process.

[0010] Furthermore, in step S1, the condensation reaction process is: firstly, the epoxy resin and the acid anhydride are heated to 70-80°C, then the inhibitor and the accelerator are added and stirred evenly, and then the temperature is slowly raised to 80-105°C and reacted for 2-4 hours.

[0011] Furthermore, in step S2, the mass ratio of the double bond-modified epoxy resin to hydroxypropyl methacrylate, methacrylic acid, sodium allyl sulfonate and hydroxyalkyl methacrylate is 30-50:25-35:5-10:10-20:5-10.

[0012] Furthermore, in step S2, during the free radical polymerization reaction, α-methylstyrene linear dimer is used as a chain transfer agent, hydroquinone is used as an inhibitor, potassium persulfate is used as an initiator, the polymerization reaction temperature is 50-70°C, the initiator is slowly added dropwise in the form of a 1% aqueous solution of potassium persulfate by mass, and the addition time is controlled at 90-120 min. After the initiator is added dropwise, the constant temperature reaction is continued for 150-200 min. After the reaction is completed, the reaction is neutralized with sodium hydroxide solution to a pH of 7-8 to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

[0013] Furthermore, the mass ratio of the chain transfer agent, the polymerization inhibitor, the initiator and the double-bond modified epoxy resin is 0.1-0.3: 0.2-0.5: 0.4-0.8: 30-50.

[0014] The surface coating of the present invention can be prepared by simple mechanical stirring. For example, firstly, the raw materials in the powder component A are mechanically stirred and mixed evenly; then, the raw materials in the liquid component B are mechanically stirred and mixed evenly; finally, the powder component A and the liquid component B are mixed according to proportion and mechanically stirred to prepare the surface coating.

[0015] Furthermore, the ordinary Portland cement has a strength grade of 42.5.

[0016] Furthermore, the specification of the double fly powder is 800 mesh.

[0017] Furthermore, the particle size of the silica fume powder is 0.2-0.4 μm.

[0018] Furthermore, the superplasticizer is a melamine-based high-efficiency water reducing agent.

[0019] Furthermore, the anti-settling agent is sarcosine.

[0020] Furthermore, the nano cerium oxide particle size is 30-50nm, and the cerium oxide content is 99.99%. Inorganic nano cerium oxide particles have good chemical stability, thermal stability, non-toxicity, corrosion resistance, and more importantly, they have strong ultraviolet absorption ability, which significantly improves the anti-ultraviolet aging performance of the polymer coating and can also improve the corrosion resistance of the polymer coating.

[0021] Furthermore, the silicate is at least one of sodium silicate, lithium silicate and potassium silicate.

[0022] Furthermore, the percentage of fluorine in the aqueous fluorocarbon emulsion is 10%, and the fluorocarbon emulsion has ultra-long weather resistance, UV resistance, excellent water resistance, acid, alkali, and salt corrosion resistance, and does not change under acid rain, air pollution, and marine salt spray corrosion conditions. The protective coating modified by fluorocarbon emulsion can significantly improve its weather resistance and corrosion resistance, resist staining, do not turn yellow, maintain a stable appearance, and can effectively protect the wind power concrete tower, improve the durability of the wind power concrete tower, and extend the service life of the wind power concrete tower.

[0023] Furthermore, the defoaming agent is Airex 901 W from German company Digo.

[0024] Furthermore, the fungicide is QK-20 from Dow Chemical.

[0025] The present invention introduces an epoxy resin with a highly active epoxy group into a copolymer to obtain an epoxy-modified acrylic copolymer with a rich epoxy group in the side chain. The epoxy group is a highly active reactive polar group, which can act on the concrete base surface through physical action or chemical bonding, and can greatly improve the bonding strength with the concrete interface; the introduction of a sulfonic acid strong polar group can act on the concrete base surface through physical action or electrostatic bonding, and can also improve the bonding strength; the copolymer polymer has a chain structure, good flexibility, and a good elongation at break, and can resist a certain deformation, thereby improving the crack resistance. Fluorocarbon polymers have ultra-long weather resistance, UV resistance, excellent water resistance, acid, alkali, and salt corrosion resistance. The protective surface coating modified by fluorocarbon emulsion can significantly improve its weather resistance and corrosion resistance, resist staining, and does not yellow, and maintains a stable appearance. By utilizing silicate to react with calcium ions in cement hydration products to generate a gel, a physical filling effect can be played, and the porosity of the concrete surface is significantly reduced, so as to fill the pore channels and improve the impermeability of the concrete. The epoxy-modified acrylic emulsion of the present invention is compounded with the water-based fluorocarbon emulsion by introducing reasonable functional group components to give full play to the advantages of each. Under the action of cement, the epoxy-modified acrylic emulsion has both the rigidity generated by cement hydration and the flexibility generated by polymer film formation, so that the prepared surface coating has excellent bonding performance, crack resistance, weather resistance, waterproof performance and corrosion resistance, effectively protects the surface of the wind power concrete tower, improves the durability of the wind power concrete tower, and prolongs the service life of the wind power concrete tower.

[0026] The technical solution of the present invention brings beneficial effects: 1) The surface coating of the present invention is prepared by synthesizing and modifying epoxy resin to prepare epoxy-modified acrylic emulsion. The epoxy groups can combine with the polar groups on the concrete interface to form chemical bonds, thereby greatly improving the bonding performance and making the bonding between the coating and the concrete tower base of the wind power tower more firmly.

[0027] 2) The surface coating of the present invention, by introducing water-based fluorocarbon emulsion, the fluorocarbon polymer has ultra-long weather resistance, UV resistance, excellent water resistance, acid, alkali and salt corrosion resistance, and does not change under acid rain, air pollution, and marine salt spray corrosion conditions. The protective surface coating modified by fluorocarbon emulsion can significantly improve its weather resistance and corrosion resistance, resist staining, do not yellow, and maintain a stable appearance.

[0028] 3) The surface coating of the present invention introduces epoxy-modified acrylic polymer and fluorocarbon polymer. The polymer macromolecule has a chain structure, good flexibility, and good elongation at break, and can resist certain deformation, thereby improving the anti-cracking performance of the coating.

[0029] 4) The surface coating of the present invention can play a physical filling role by utilizing silicate to react with calcium ions in cement hydration products of the concrete base surface to generate gel, which can significantly reduce the porosity of the concrete surface, thereby filling the pore channels and improving the anti-seepage performance of the concrete.

[0030] In summary, the present invention achieves synergistic effects through scientific combination of various components, so that the surface coating used for the protection of wind power hybrid tower concrete tower has the characteristics of good bonding performance, excellent crack resistance, good corrosion resistance, strong weather resistance and good durability. It is suitable for the surface protection of wind power hybrid tower concrete tower, can improve the durability of wind power hybrid tower concrete tower, and extend the service life of wind power hybrid tower concrete tower. DETAILED DESCRIPTION

[0031] The present invention is further illustrated by the following examples, but the protection scope of the present invention is not limited to the following examples.

[0032] In the following specific examples, unless otherwise specified, all raw materials are directly purchased commercial raw materials. For example, melamine-based high-efficiency water reducer was purchased from BASF, Germany; water-based fluorocarbon emulsion was purchased from Shanghai Deyude Trading Co., Ltd.; fungicide was purchased from Dow Chemical, etc.

[0033] Example 1

[0034] 1. Preparation of epoxy modified acrylic emulsion: (1) 45 parts of bis((3,4-epoxycyclohexyl)methyl)adipate and 10 parts of itaconic anhydride were put into a reaction kettle, stirred, and heated to 70°C. Then, 2 parts of N,N-dipropyl-1-propylamine accelerator and 0.03 parts of hydroquinone were added and stirred evenly. The temperature was then slowly raised to 100°C. The reaction was stirred for 4 hours under the action of the accelerator and the inhibitor, and the temperature was then lowered to 30°C to prepare an unsaturated epoxy resin. (2) 30 parts of the obtained unsaturated epoxy resin monomer were mixed with 35 parts of hydroxypropyl methacrylate, 10 parts of methacrylic acid, 15 parts of sodium allyl sulfonate and 10 parts of hydroxyalkyl methacrylate, 0.1 parts of α-methylstyrene linear dimer was used as a chain transfer agent, 0.2 parts of hydroquinone was used as an inhibitor, and 50 parts of a 1% by mass potassium persulfate aqueous solution was used as an initiator. The polymerization reaction was carried out at 70°C. The initiator was added in a slow dropwise manner and the addition was completed within 120 minutes. The reaction was continued at a constant temperature for 200 minutes. (3) After the reaction is completed, 3 parts of 20% by mass sodium hydroxide solution are used to neutralize the mixture to a pH of 7 to 8 to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

[0035] 2. Preparation of a surface coating: Step 1: Preparation of powder component A: 30 parts of ordinary Portland cement, 55 parts of double fly ash, 10 parts of silica fume, 1.5 parts of melamine-based high-efficiency water reducer, 0.1 parts of anti-settling agent sarcosine, 0.5 parts of nano cerium oxide, and 5 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 30 parts of epoxy-modified acrylic emulsion, 35 parts of water-based fluorocarbon emulsion, 0.5 parts of fungicide, and 0.5 parts of defoamer into 35 parts of deionized water, and stir mechanically at 500 r / min to make them uniform; Step 3: Add 100 parts of powder component A to 70 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0036] Example 2

[0037] 1. Preparation of epoxy modified acrylic emulsion: (1) 55 parts of bis((3,4-epoxycyclohexyl)methyl)adipate and 6 parts of itaconic anhydride were put into a reaction kettle, stirred, and heated to 75°C. Then, 4 parts of N,N-dipropyl-1-propylamine accelerator and 0.04 parts of hydroquinone were added and stirred evenly. The temperature was then slowly raised to 90°C. The reaction was stirred for 4 hours under the action of the accelerator and the inhibitor, and the temperature was then lowered to 30°C to prepare an unsaturated epoxy resin. (2) 40 parts of the obtained unsaturated epoxy resin monomer were mixed with 30 parts of hydroxypropyl methacrylate, 10 parts of methacrylic acid, 10 parts of sodium allyl sulfonate and 10 parts of hydroxyalkyl methacrylate, 0.2 parts of α-methylstyrene linear dimer was used as a chain transfer agent, 0.3 parts of hydroquinone was used as an inhibitor, and 40 parts of a 1% by mass potassium persulfate aqueous solution was used as an initiator. The polymerization reaction was carried out at 60°C. The initiator was added in a slow dropwise manner and the addition was completed within 105 minutes. The reaction was continued at a constant temperature for 180 minutes. (3) After the reaction is completed, 3 parts of 20% by mass sodium hydroxide solution are used to neutralize the mixture to a pH of 7 to 8 to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

[0038] 2. Preparation of a surface coating: Step 1: Preparation of powder component A: 50 parts of ordinary Portland cement, 40 parts of double fly ash, 5 parts of silica fume, 1.0 part of melamine-based high-efficiency water reducer, 0.2 parts of anti-settling agent sarcosine, 0.8 parts of nano cerium oxide, and 5 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 45 parts of epoxy-modified acrylic emulsion, 25 parts of water-based fluorocarbon emulsion, 0.5 parts of fungicide, and 0.5 parts of defoamer into 30 parts of deionized water, and stir mechanically at 500 r / min to make them uniform; Step 3: Add 100 parts of powder component A to 60 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0039] Example 3

[0040] 1. Preparation of epoxy modified acrylic emulsion: (1) 60 parts of bis((3,4-epoxycyclohexyl)methyl)adipate and 3 parts of itaconic anhydride were put into a reaction kettle, stirred, and heated to 80°C. Then, 6 parts of N,N-dipropyl-1-propylamine accelerator and 0.05 parts of hydroquinone were added and stirred evenly. The temperature was then slowly raised to 80°C. The reaction was stirred for 4 hours under the action of the accelerator and the inhibitor, and the temperature was then lowered to 30°C to prepare an unsaturated epoxy resin. (2) 50 parts of the obtained unsaturated epoxy resin monomer were mixed with 25 parts of hydroxypropyl methacrylate, 5 parts of methacrylic acid, 15 parts of sodium allyl sulfonate and 5 parts of hydroxyalkyl methacrylate, 0.3 parts of α-methylstyrene linear dimer was used as a chain transfer agent, 0.5 parts of hydroquinone was used as an inhibitor, and 80 parts of a 1% by mass potassium persulfate aqueous solution was used as an initiator. The polymerization reaction was carried out at 50°C. The initiator was added in a slow dropwise manner and the addition was completed within 90 minutes. The reaction was continued at a constant temperature for 200 minutes. (3) After the reaction is completed, the mixture is neutralized to pH 7-8 with 2 parts by mass of 20% sodium hydroxide solution to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

[0041] 2. Preparation of a surface coating: Step 1: Preparation of powder component A: 60 parts of ordinary Portland cement, 30 parts of double fly ash, 4 parts of silica fume, 0.5 parts of melamine-based high-efficiency water reducer, 0.3 parts of anti-settling agent sarcosine, 1.0 parts of nano cerium oxide, and 6 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 55 parts of epoxy-modified acrylic emulsion, 20 parts of water-based fluorocarbon emulsion, 0.2 parts of fungicide, and 1.0 parts of defoamer into 25 parts of deionized water, and stir mechanically at 500 r / min to make them uniform; Step 3: Add 100 parts of powder component A to 80 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that the epoxy-modified acrylic emulsion in liquid material B is replaced by acrylic emulsion, that is, the emulsion does not contain epoxy groups. Specifically: Preparation of acrylic emulsion: (1) 30 parts of itaconic anhydride were mixed with 35 parts of hydroxypropyl methacrylate, 10 parts of methacrylic acid, 15 parts of sodium allyl sulfonate and 10 parts of hydroxyalkyl methacrylate, 0.1 parts of α-methylstyrene linear dimer was used as a chain transfer agent, 0.2 parts of hydroquinone was used as an inhibitor, and 50 parts of a 1% by mass potassium persulfate aqueous solution was used as an initiator. The polymerization reaction was carried out at 70°C. The initiator was added in a slow dropwise manner and the addition was completed within 120 minutes. The reaction was continued at a constant temperature for 200 minutes. (2) After the reaction is completed, 3 parts of 20% by mass sodium hydroxide solution are used to neutralize to pH = 7-8 to obtain an acrylic emulsion.

[0043] 2. Preparation of a surface coating: Step 1: Preparation of powder component A: 30 parts of ordinary Portland cement, 55 parts of double fly ash, 10 parts of silica fume, 1.5 parts of melamine-based high-efficiency water reducer, 0.1 parts of anti-settling agent sarcosine, 0.5 parts of nano cerium oxide, and 5 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 30 parts of acrylic emulsion, 35 parts of water-based fluorocarbon emulsion, 0.5 parts of fungicide, and 0.5 parts of defoamer into 35 parts of deionized water, and stir mechanically at 500 r / min until uniform; Step 3: Add 100 parts of powder component A to 70 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that liquid material B does not contain epoxy-modified acrylic emulsion. Specifically: 1. Preparation of a surface coating: Step 1: Preparation of powder component A: 30 parts of ordinary Portland cement, 55 parts of double fly ash, 10 parts of silica fume, 1.5 parts of melamine-based high-efficiency water reducer, 0.1 parts of anti-settling agent sarcosine, 0.5 parts of nano cerium oxide, and 5 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 65 parts of aqueous fluorocarbon emulsion, 0.5 parts of fungicide, and 0.5 parts of defoamer into 35 parts of deionized water, and stir mechanically at 500 r / min until uniform; Step 3: Add 100 parts of powder component A to 70 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that liquid material B does not contain aqueous fluorocarbon emulsion. Specifically: 1. Preparation of epoxy modified acrylic emulsion: (1) 45 parts of bis((3,4-epoxycyclohexyl)methyl)adipate and 10 parts of itaconic anhydride were put into a reaction kettle, stirred, and heated to 70°C. Then, 2 parts of N,N-dipropyl-1-propylamine accelerator and 0.03 parts of hydroquinone were added and stirred evenly. The temperature was then slowly raised to 100°C. The reaction was stirred for 4 hours under the action of the accelerator and the inhibitor, and the temperature was then lowered to 30°C to prepare an unsaturated epoxy resin. (2) 30 parts of the obtained unsaturated epoxy resin monomer were mixed with 35 parts of hydroxypropyl methacrylate, 10 parts of methacrylic acid, 15 parts of sodium allyl sulfonate and 10 parts of hydroxyalkyl methacrylate, 0.1 parts of α-methylstyrene linear dimer was used as a chain transfer agent, 0.2 parts of hydroquinone was used as an inhibitor, and 50 parts of a 1% by mass potassium persulfate aqueous solution was used as an initiator. The polymerization reaction was carried out at 50°C. The initiator was added in a slow dropwise manner and the addition was completed within 120 minutes. The reaction was continued at a constant temperature for 200 minutes. (3) After the reaction is completed, 3 parts of 20% by mass sodium hydroxide solution are used to neutralize the mixture to a pH of 7 to 8 to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

[0046] 2. Preparation of a surface coating: Step 1: Preparation of powder component A: 30 parts of ordinary Portland cement, 55 parts of double fly ash, 10 parts of silica fume, 1.5 parts of melamine-based high-efficiency water reducer, 0.1 parts of anti-settling agent sarcosine, 0.5 parts of nano cerium oxide, and 5 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 65 parts of epoxy-modified acrylic emulsion, 0.5 parts of fungicide, and 0.5 parts of defoamer into 35 parts of deionized water, and stir mechanically at 500 r / min to make them uniform; Step 3: Add 100 parts of powder component A to 70 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0047] Comparative Example 4 The difference between this comparative example and Example 1 is that the powder A does not contain nano cerium oxide. Specifically: 1. Preparation of epoxy modified acrylic emulsion: (1) 45 parts of bis((3,4-epoxycyclohexyl)methyl)adipate and 10 parts of itaconic anhydride were put into a reaction kettle, stirred, and heated to 70°C. Then, 2 parts of N,N-dipropyl-1-propylamine accelerator and 0.03 parts of hydroquinone were added and stirred evenly. The temperature was then slowly raised to 100°C. The reaction was stirred for 4 hours under the action of the accelerator and the inhibitor, and the temperature was then lowered to 30°C to prepare an unsaturated epoxy resin. (2) 30 parts of the obtained unsaturated epoxy resin monomer were mixed with 35 parts of hydroxypropyl methacrylate, 10 parts of methacrylic acid, 15 parts of sodium allyl sulfonate and 10 parts of hydroxyalkyl methacrylate, 0.1 parts of α-methylstyrene linear dimer was used as a chain transfer agent, 0.2 parts of hydroquinone was used as an inhibitor, and 50 parts of a 1% by mass potassium persulfate aqueous solution was used as an initiator. The polymerization reaction was carried out at 50°C. The initiator was added in a slow dropwise manner and the addition was completed within 120 minutes. The reaction was continued at a constant temperature for 200 minutes. (3) After the reaction is completed, 3 parts of 20% by mass sodium hydroxide solution are used to neutralize the mixture to a pH of 7 to 8 to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

[0048] 2. Preparation of a surface coating: Step 1: Preparation of powder component A: 30 parts of ordinary Portland cement, 55 parts of double fly ash, 10 parts of silica fume, 1.5 parts of melamine-based high-efficiency water reducer, 0.1 parts of anti-settling agent sarcosine, and 5 parts of sodium silicate. Mechanically stir and mix the above raw materials evenly; Step 2, preparation of liquid component B: add 30 parts of epoxy-modified acrylic emulsion, 35 parts of water-based fluorocarbon emulsion, 0.5 parts of fungicide, and 0.5 parts of defoamer into 35 parts of deionized water, and stir mechanically at 500 r / min to make them uniform; Step 3: Add 100 parts of powder component A to 70 parts of liquid component B, and stir mechanically for 3 minutes to obtain a surface coating.

[0049] During construction, the powder component A and the liquid component B are mixed evenly in proportion and can be used. Adhesion, alkali resistance, acid resistance and frost resistance are tested according to the method of JG / T 335-2011 "Film-forming coating for concrete structure protection", water resistance and weather resistance are tested according to the method of JT / T 695-2007 "Technical conditions for corrosion protection of concrete bridge structure surface coating", and elongation at break is tested according to the method of GB / T16777-2008 "Test methods for building waterproof coatings". The test results of various performances are shown in Table 1.

[0050] Table 1 Performance test results of various embodiments and comparative examples

[0051] The results show that Example 1, Example 2, and Example 3 have good mechanical properties, excellent adhesion, good elongation at break, can achieve good anti-cracking effect, have excellent water resistance, alkali resistance, acid resistance, weather resistance and frost resistance, and good corrosion resistance. They can effectively protect the surface of the wind turbine concrete tower, improve the durability of the wind turbine concrete tower, and extend the service life of the wind turbine concrete tower.

[0052] The adhesion of the polymers without epoxy groups in Comparative Examples 1 and 2 is greatly reduced, indicating that the epoxy groups have a significant effect on the bonding performance.

[0053] In Comparative Example 2, only the water-based fluorocarbon emulsion is present, and the elongation at break is greatly reduced, indicating that the elongation at break performance of the water-based fluorocarbon emulsion is average, and it needs to be compounded with an acrylic emulsion with high elongation performance to achieve the best effect.

[0054] Comparative Example 3 does not contain aqueous fluorocarbon emulsion, and the corrosion resistance and weather resistance are significantly reduced, indicating that the aqueous fluorocarbon emulsion has a significant effect on the corrosion resistance and weather resistance of the coating.

[0055] The weather resistance of Comparative Example 4 has a certain decline, indicating that the anti-ultraviolet aging property of nano-cerium oxide has a certain influence on the weather resistance of the coating.

[0056] To sum up, scientific and reasonable compounding is a necessary condition for preparing a surface coating with excellent performance. When the components of the surface coating for protecting the wind power hybrid tower concrete tower of the present invention reach a scientific balance condition, they can exert the best synergistic effect, so that it has the characteristics of good bonding performance, excellent crack resistance, good corrosion resistance, strong weather resistance and good durability. It is suitable for the surface protection of wind power hybrid tower concrete tower, improves the durability of wind power hybrid tower concrete tower, and prolongs the service life of wind power hybrid tower concrete tower.

Claims

1. A surface coating for protecting a wind power concrete tower, characterized in that: Including powder component A and liquid component B: The powder A component includes the following components in parts by weight: 30~60 parts of ordinary Portland cement; 30~55 portions of double fly powder; Silica fume powder 4-10 parts; Superplasticizer 0.5~1.5 parts; Anti-settling agent 0.1~0.3 parts; 0.3~1 part of nano cerium oxide; 3-6 parts of silicate; The liquid material B component includes the following components in parts by weight: Epoxy modified acrylic emulsion 30-55 parts; 20~35 parts of water-based fluorocarbon emulsion 20~40 parts of deionized water; 0.2~0.5 parts of fungicide; Defoaming agent 0.5~2 parts; The mass ratio of the powder component A to the liquid component B is 100:60-80.

2. The surface coating according to claim 1, characterized in that The preparation steps of the epoxy modified acrylic emulsion are as follows: S1, mixing an epoxy resin with an acid anhydride containing a double bond, and carrying out a condensation reaction under the action of a promoter and an inhibitor to obtain a double-bond modified epoxy resin; S2. Mix the double-bond modified epoxy resin with hydroxypropyl methacrylate, methacrylic acid, sodium allyl sulfonate and hydroxyalkyl methacrylate, and carry out free radical polymerization under the action of an initiator, a chain transfer agent and an inhibitor to obtain an epoxy-modified acrylic emulsion.

3. The surface coating according to claim 2, characterized in that In step S1, the epoxy resin is bis((3,4-epoxycyclohexyl)methyl)adipate.

4. The surface coating according to claim 2, characterized in that In step S1, the acid anhydride containing a double bond is itaconic anhydride, and the mass ratio of the acid anhydride to the epoxy resin is 3-10:45-60.

5. The surface coating according to claim 2, characterized in that In step S1, N,N-dipropyl-1-propylamine is used as a promoter, hydroquinone is used as an inhibitor, and the mass ratio of the promoter, the inhibitor and the epoxy resin is 2-6: 0.03-0.05: 45-60.

6. The surface coating according to claim 2, characterized in that In step S1, the condensation reaction process is: first, the epoxy resin and the acid anhydride are heated to 70-80°C, then the inhibitor and the accelerator are added and stirred evenly, and then the temperature is slowly raised to 80-105°C and reacted for 2-4 hours.

7. The surface coating according to claim 2, characterized in that In step S2, the mass ratio of the double bond modified epoxy resin to hydroxypropyl methacrylate, methacrylic acid, sodium allyl sulfonate and hydroxyalkyl methacrylate is 30-50:25-35:5-10:10-20:5-10.

8. The surface coating according to claim 2, characterized in that In step S2, during the free radical polymerization reaction, α-methylstyrene linear dimer is used as a chain transfer agent, hydroquinone is used as an inhibitor, potassium persulfate is used as an initiator, the polymerization reaction temperature is 50-70°C, the initiator is slowly added dropwise in the form of a 1% aqueous solution of potassium persulfate by mass, and the addition time is controlled at 90-120min. After the initiator is added dropwise, the constant temperature reaction is continued for 150-200min. After the reaction is completed, the reaction is neutralized with sodium hydroxide solution to a pH of 7-8 to obtain an epoxy-modified acrylic emulsion containing epoxy groups on the side chains.

9. The surface coating according to claim 2, characterized in that The mass ratio of the chain transfer agent, the polymerization inhibitor, the initiator and the double-bond modified epoxy resin is 0.1-0.3: 0.2-0.5: 0.4-0.8: 30-50.

10. The surface coating according to claim 2, characterized in that The ordinary Portland cement has a strength grade of 42.5; The specification of the double fly powder is 800 mesh; The particle size of the silica fume powder is 0.2-0.4 μm; The superplasticizer is a melamine-based high-efficiency water reducer; The anti-settling agent is sarcosine; The nano-cerium oxide has a particle size of 30-50 nm and a cerium oxide content of 99.99%; The silicate is at least one of sodium silicate, lithium silicate and potassium silicate; The content of fluorine in the aqueous fluorocarbon emulsion is 10%.

Citation Information

Patent Citations

  • Waterborne polymer cement-based waterproof coating and preparation method thereof

    CN107523150A

  • Surface permeation type waterproof coating and preparation method thereof

    CN116102311A

  • Surface sealing coating for repairing concrete cracks

    CN117645502A